Optimisasi Energi Melalui Pelatihan Mekanisasi Sistem Kontrol Mobil Listrik: Sebuah Pendekatan PKM - Amiruddin; Hidayat, Akmal; Iris Sumariyanto; Muhammad Hasim S; Muhammad Haristo Rahman (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The increasing population growth and demand for transportation energy in Indonesia, particularly from fossil fuel-powered vehicles, highlight the urgency of adopting environmentally friendly technologies. The government's focus on electric vehicles is promising, but it requires competent human resources support. The Community Service Program (PKM) titled "Energy Optimization Through Mechanization Training for Vehicle Control Systems: A PKM Approach" at the Faculty of Engineering, Universitas Negeri Makassar, has made a significant contribution. Through the PKM approach, students are actively engaged, enhancing their knowledge and practical skills in implementing energy-efficient technology. The outcomes include improved assembly and integration skills for control system mechanisms and the implementation of technology in personal vehicles. This training also raises environmental awareness and empowers students as agents of change. Positive evaluations from aspects of knowledge, skills, and social impact support the importance of developing competent human resources to facilitate the advancement of energy-efficient vehicle technology in Indonesia.